Implementasi Tri Hita Karana Sebagai Budaya Organisasi di The Royal Pita Maha Hotel - Ni Putu Yunita Anggreswari; A. A. N. Oka Suryadinatha Gorda (Jayapangus Press, 2020)
Tri Hita Karana is a Hindu concept that has the understanding of the three causes of human welfare consisting of three elements which include Parhyangan, namely the Godhead, the Pawongan element of Humanity and the Palemahan the environmental elements. Tri Hita Karana is treated as an organizational culture in The Royal Pita Maha Hotel which is then applied by all members of the organization as a standard of behavior. The formulation of the problem in this study is